Construction and demolition waste management by Baixo Alentejo construction companies - Ramos, Mário (2021)
This report presents the results of a participatory workshop conducted with representatives of micro and small construction companies in the Baixo Alentejo region of Portugal, highlighting the importance of a common regulatory framework for construction and demolition waste (CDW) management at the local level.